5G highway tunnel deployment scheme and performance verification - Yan YANG; Tao ZHANG; Xirui GUO; Xiang PAN (Dianxin kexue)
The scheme of deploying highway tunnel in 3.5 GHz typical frequency band of 5G was systematically analyzed.And the performance of the new antenna and the new leaky cable deployed for highway tunnel were comprehensively evaluated by RSRP,SINR,and rate distribution.The coverage performance,safety requirements,cost and other aspects of each scheme were proposed.It made up for the current research gap in this area,provided the first-hand materials for the 5G highway tunnel deployment,and effectively promoted the equipment evolution.